The Effect of Literary Reading Program in Online Learning on Students’ Reading Ability - Nurul Lailatul Khusniyah (STAI Hubbulwathan Duri, 2022)
This study aimed to investigate the effect of the literary reading program on students’ reading abilities. This study also focused on improving reading skills in inferential and critical context aspects. An experimental design with a one-group pretest-posttest design was used in the study. 100 student from the fourth semester of the Extensive Reading Online Class was used as a sample. The researchers used a purposeful sampling method in choosing the sample in this research. This research was held at UIN Mataram's English Department from March to June 2022. Three types of data were collected during the data collection process: 1) documents, 2) observations, and 3) reading tests. The technique of analyzing data used a t-test with two samples paired. The findings of this study showed that the t-stat value is the calculated t-value, which is 7,886. While the value of P(T=t) one tail is the p-value which is 2.099 and the critical one-tail t is the t-table value which is 1.66. It means that t-stat (7.886) t table (1.66), then Ho is rejected and H1 is accepted. It concluded that the literary reading program had a positive effect on the reading skills of English students. The findings show that literary works can be used as authentic teaching materials in learning to read English, allowing students to understand the meaning of reading not only at the literal level but also at a deeper level based on context.